2020
DOI: 10.1080/19490976.2020.1799734
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation in pregnancy and early infancy in relation to gut microbiota composition and C. difficile colonization: implications for viral respiratory infections

Abstract: In Canada and the US, the infant diet is supplemented with vitamin D via supplement drops or formula. Pregnant and nursing mothers often take vitamin D supplements. Since little is known about the impact of this supplementation on infant gut microbiota, we undertook a study to determine the association between maternal and infant vitamin D supplementation, infant gut microbiota composition and Clostridioides difficile colonization in 1,157 mother-infant pairs of the CHILD (Canadian Healthy Infant Longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
1
23
0
1
Order By: Relevance
“…As described in Table 1, we found 14 interventional studies, 7 of which were randomized controlled trials (RCTs) [27][28][29][30][31][32][33]. The other 11 were observational studies, of which 4 were cohorts [34][35][36][37], 6 were cross-sectional [38][39][40][41][42][43] and 1 was a case-control study [44].…”
Section: Study Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in Table 1, we found 14 interventional studies, 7 of which were randomized controlled trials (RCTs) [27][28][29][30][31][32][33]. The other 11 were observational studies, of which 4 were cohorts [34][35][36][37], 6 were cross-sectional [38][39][40][41][42][43] and 1 was a case-control study [44].…”
Section: Study Designsmentioning
confidence: 99%
“…The populations selected were predominantly healthy and were mostly composed of volunteers and students. Five studies were conducted on cohorts of pregnant women [29,[34][35][36][37]. The other studies enrolled participants with ulcerative colitis and Crohn's disease [38,[44][45][46], followed by multiple sclerosis [47], cystic fibrosis [30], HIV [31], and prediabetes [27].…”
Section: Study Designsmentioning
confidence: 99%
“…Megamonas , Veillonella , and Haemophilus were enriched in GA. Megamonas could act as a beneficial bacterium, and it has been reported that compared to healthy microbiota, canine anal furunculosis (CAF) microbiota showed a decreased abundance of Megamonas ( Maldonado-Contreras et al., 2020 ). Nevertheless, another study illustrated infant vitamin D supplementation was associated with a lower abundance of Megamonas in gut microbiota, implying the potential competitive relationship between vitamin D and Megamonas ( Drall et al., 2020 ). Veillonella species, documented as the Fe (III)-reducing genera, were capable of supplying Fe (II) to combine with oxygen in Hb ( Jin et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…No difference was noted regarding b diversity. Prenatal maternal vitamin D supplementation (17) No association with infant Clostridium difficile colonization in crude or adjusted models Prenatal maternal milk consumption (>3 cups per day compared to less or 1 cup per day) (17) Statistical significant lower odds of Clostridium difficile colonization in exclusively breastfed infants Maternal vitamin D supplementation (18) Infant's gut microbiota is altered according to the dose of vitamin D supplementation during pregnancy Maternal consumption of vitamin D fortified milk (17) Reduced chances of Clostridium difficile colonization in infants Maternal high fruit consumption among vaginally born infants (6) Increased odds for high Streptococcus/Clostridium gut colonization Maternal diet rich in red processed meat among babies delivered by caesarian section (6) Increased numbers of Bifidobacterium in offspring.…”
Section: Factors Of Nutrition During Pregnancymentioning
confidence: 99%
“…and Clostridium difficile , underlining that the levels of vitamin D during pregnancy affect the offspring’s gut microbiota composition ( 18 ). In a subset of 1,157 mother-infant pairs of the CHILD Cohort study, maternal consumption of vitamin-D fortified milk was associated with reduced the likelihood of C. difficile colonization in infants ( 17 ).…”
Section: Effects Of Maternal Nutrition During Pregnancy On the Infantmentioning
confidence: 99%